Comparative investigation on thermochemical energy storage stability of Zr/Al-supported dark CaO-based composites under harsh energy storage mode - Keke Li; Ruichang Xu; Jian Sun; Yuge Cui; Jianghua Liu; Shuoyu Yang; Ruilin Wang; Zijian Zhou; Xinming Nie (Carbon Capture Science & Technology, 2022)
CaO-based materials are potential candidates for thermochemical energy storage in calcium looping (CaL) due to their low-cost and large theoretical heat storage capacity. The harsh energy storage mode can circumvent adopting the membrane separation techniques with uncertain availability, contributing to improve the practicability of CaL. Nevertheless, the high calcination temperature and CO2 partial pressure involved in harsh energy storage mode adversely affect the cyclic stability of CaO-based materials. Therefore, comparison investigation on cyclic stability of CaO-based composites with inert supports for energy storage under harsh mode (950 °C, pure CO2) was conducted. The single Zr-supported, CaO-based composite possesses the highest energy release density of 1.42 MJ/kg after 19 cycles, which is markedly higher than that of the single Al- or Zr/Al-supported CaO-based composites. The Fe/Mn-doped, Zr-supported CaO-based composites were further prepared aiming to achieve direct solar absorption in the CaL. Although the binary Fe/Mn ions doping causes the decreased energy release density due to consumption of active CaO, the optical adsorption capability is significantly enhanced. The dark composite with a molar ratio of Ca/Zr:Fe:Mn = 100:4:8 exhibits the highest spectral absorbance of 74.2%, which is approximately 5.8 times that of white Zr-supported CaO-based composite. It also possesses excellent energy storage/release stability with a low average energy release density loss of 0.005 MJ/kg per cycle during 19 cycles.